Motivasi Kerja Memediasi Budaya Organisasi terhadap Kinerja - Erika Febianasari Dewi; Kustini Kustini (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study is to examine variable of Organizational Culture, and Competence have effect on Employee Performance by Motivation Variables at Department of Library and Archives East Java. This research uses quantitative approach and the method used is descriptive method, data collection techniques and field research consisting of observation, interview, and questionnare distributed to the respondents by google form. The population in this study used employee of Department of Library and Archive East Java. The sampling in this study used nonprobability sampling using a purposive sampling approach as much a 54 employees. This study analyzed using Smart Partial Last Square. The result of this study shows that Organizational Culture have Affect on Employee Performance, Competence does not have affect on employee performance, Organizational culture have affect on Motivation, Competence have affect on Motivation, Motivation have affect on employee Performance, Motivation can mediate Organizational Culture on Employee performance, and Motivation can’t mediate competence on employee performance at Department of Library and Archives East Java.